2020
DOI: 10.3390/ijms21072398
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cystic Fibrosis Patients Homozygous for F508del with Lumacaftor-Ivacaftor (Orkambi®) Restores Defective CFTR Channel Function in Circulating Mononuclear Cells

Abstract: The treatment of cystic fibrosis (CF) patients homozygous for the F508del mutation with Orkambi®, a combination of a corrector (lumacaftor) and a potentiator (ivacaftor) of the mutated CFTR protein, resulted in some amelioration of the respiratory function. However, a great variability in the clinical response was also observed. The aim of this study was to evaluate the response to Orkambi® in a small cohort of F508del/F508del patients (n = 14) in terms of clinical and laboratory parameters, including ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
(51 reference statements)
2
22
0
4
Order By: Relevance
“…Reduced bacterial diversity in PWCF is typically associated with increasing age; however, young children with CF have decreased airway microbial diversity compared to healthy children of the same age [ 148 ]. In children with CF, modulators have been shown to improve bacterial diversity to a state similar to that of healthy individuals (IVA and TEZ/IVA) [ 149 ], with similar findings in adults with the G551D mutation taking IVA [ 117 , 118 , 150 ]. However, only small numbers of patients have been studied, and as established microbial communities may take time to adjust, larger longitudinal microbiome studies are needed to assess the long-term effects on the microbiome.…”
Section: Cftr Modulators the Microbiome And Airway Infectionmentioning
confidence: 87%
See 4 more Smart Citations
“…Reduced bacterial diversity in PWCF is typically associated with increasing age; however, young children with CF have decreased airway microbial diversity compared to healthy children of the same age [ 148 ]. In children with CF, modulators have been shown to improve bacterial diversity to a state similar to that of healthy individuals (IVA and TEZ/IVA) [ 149 ], with similar findings in adults with the G551D mutation taking IVA [ 117 , 118 , 150 ]. However, only small numbers of patients have been studied, and as established microbial communities may take time to adjust, larger longitudinal microbiome studies are needed to assess the long-term effects on the microbiome.…”
Section: Cftr Modulators the Microbiome And Airway Infectionmentioning
confidence: 87%
“…Ex vivo studies have revealed direct effects of CFTR modulators on the function of neutrophils [ 69 , 109 , 124 , 125 ], macrophages [ 126 , 127 , 130 ], lymphocytes [ 131 , 132 , 133 ], epithelial cells [ 134 , 135 ], and their signalling pathways [ 124 , 128 , 132 ]. There have been additional effects of CFTR modulators demonstrating improvements in MCC including LCI, mucus plugging, and air trapping [ 117 , 121 , 122 ], as well as effects on ciliary function [ 143 ]. However, despite these findings, uncertainty remains as to whether these effects are directly attributable to modulator effects on target cells or whether they are secondary to modification of the diseased airway environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations